Development and Evaluation of the Acaricidal Activity of Xantan Gum-Based Hydrogel and Polymeric Nanoparticles Containing Achyrocline satureioides Extract - Fantatto, Rafaela Regina [UNESP]; Gomes, Annelize Rodrigues [UNESP]; Constantini, João Vitor Carvalho [UNESP]; Rodero, Camila Fernanda [UNESP]; Chorilli, Marlus [UNESP]; Chagas, Ana Carolina de Souza; Melero, Ana; Pietro, Rosemeire Cristina Linhari Rodrigues [UNESP] (MDPI, 2024)
The Rhipicephalus microplus tick causes enormous economic losses in livestock farming around the world. Despite several promising studies carried out with plant extracts such as Achyrocline satureioides against this ectoparasite, a major obstacle is related to pharmaceutical presentation forms. There is no study showing xantan gum-based hydrogel and polycaprolactone nanoparticles containing A. satureioides extract against R. microplus larvae. The objective of this study was to incorporate A. satureioides extract to develop a nanoformulation (AScn) and a hydrogel (ASlh) and evaluate them against R. microplus larvae with the purpose of increasing the contact time of the extract with the larvae and improve the effectiveness. The ethanolic extracts were incorporated in polycaprolactone nanoparticles and characterized via analysis of the mean hydrodinamic diameter and polidispersity index. The xanthan gum-based hydrogel formulation was prepared with crude extract of A. satureioides 40 mg/mL, 0.25% xanthan gum, and 8% poloxamer, to determine the bioadhesiveness of the formulation in bovine leather and the flow rate of the formulation in the animal. The results in larvae demonstrated that when evaluated in the form of a hydrogel (ASlh), mortality was higher, with 91.48% mortality at a concentration of 20 mg/mL presenting itself as an interesting alternative for controlling this ectoparasite.
Keywords: acaricidal activity; Achyrocline satureioides; hydrogel; Rhipicephalus microplus; xanthan gum